„A magyar nemzet Cato-ja”: Irányi Dániel pécsi képviselő küzdelme a vallásszabadságért és a polgári házasságért - Kasuba, Róbert István (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
Dániel Irányi is one of the most important jurists and politicians of Hungary in the era of dualism. From 1848 to 1892 he was a member of the Hungarian National Assembly. The life and work of the statesman is exemplary. Because of his perseverance, he was called the Hungarian Cato. I present his 24-year struggle in the Parliament for the freedom of religion and civil marriage. His continuous efforts gained meaning in 1869 by the submission of a bill on religious freedom, but he received final reassurance only much later, in 1892, when his bill was accepted. I analyse the bill and the related parliamentary debate, and the counterproposals submitted by József Eötvös and Kálmán Tisza. I point out the reasons why the Parliament could not accept any of the proposals in 1869. The purpose of my research is to demonstrate the path that led Hungarian legal thinking to the creation of the marriage law and the law on religious freedom in 1894 and 1895.